A novel vulnerability model considering synergistic effect of fire and overpressure in chemical processing facilities. (January 2022) - Ding, Long; Khan, Faisal; Ji, Jie
Highlights: A novel vulnerability model for fire and explosion synergistic effect model is proposed. The model enables equipment's vulnerability under the spatial-temporal synergistic effect of heat and overpressure. The application of the model is demonstrated using case study, which confirms that the model results closer to reality. The model will serve as a rapid quantitative risk assessment tool for the domino effect. Abstract: Processing facilities are faced with spatial-temporal dependent multiple-hazards. These hazards could cause catastrophic consequences. A novel vulnerability model called the "fire and explosion synergistic effect model" (FESEM) is proposed in the present study to model equipment vulnerability under the spatial-temporal synergistic of heat radiation and overpressure. On the basis of the fire synergistic effect model, the FESEM firstly model the temperature elevation and the yield strength reduction of the storage tank wall under fire heat radiation. Then, based on the von Mises yield criterion, the FESEM models the equivalent stress under overpressure. Combining the lowered yield strength induced by fire heat radiation and equivalent stress induced by overpressure under the synergistic effect, the logistic function is used to estimate time to failure and escalation probability. The application of the model is demonstrated in the case study, which confirms that the synergistic effect is significant and closer to reality. The parameters that have considerable effects on time to failure and escalation probability are discussed. The proposed method will serve as a rapid quantitative risk assessment tool of multi-hazard coupling, including the domino effect. The model will serve as an essential guide for preventing and controlling domino effects.